Optical density of Scots pine wood and climatic conditions in Toruń, Poland - Pospieszyńska, Aleksandra; Koprowski, Marcin; Przybylak, Rajmund Krzysztof (Bulletin of Geography. Physical Geography Series, 2018)
The aim of the studies was to evaluate the usefulness of the microscopic features of wood in characterising the climatic conditions of a period for which only proxy data are available. Samples were taken from historical wood from Koronowo collegiate church and from a living Scots pine tree growing in the Toruń-Wrzosy site. All measurements were performed using ImageJ software. The dendroclimatological analysis was carried out in the program DendroClim2002. The results show a correlation between the microscopic features of wood and climatic conditions. For the period 1951–2000 the maximum optical density of pine wood depends on average May air temperature and June rainfall, with correlation coefficients of -0.32 and -0.29, respectively. A similar correlation was found for mean maximum and minimum temperatures in May; -0.35 and -0.37, respectively. Additional correlations between selected meteorological elements and the maximum optical density of the wood were found using 30-year moving averages and moving intervals.